Old dogs, new tricks? A Norwegian study on whether previous collaboration exercise experience impacted participant's perceived exercise effect. Issue 2 (28th November 2018) - Sorensen, Jarle Lowe; Carlström, Eric D.; Magnussen, Leif Inge; Kim, Tae-eun; Christiansen, Atle Martin; Torgersen, Glenn-Egil
Abstract : Purpose: The purpose of this paper is to investigate the perceived effects of a maritime cross-sector collaboration exercise. More specifically, this study aims to examine whether past exercise experience had an impact on the operative exercise participant's perceived levels of collaboration, learning and usefulness. Design/methodology/approach: This was a non-experimental quantitative survey-based study. A quantitative methodology was chosen over qualitative or mixed-methods methodologies as it was considered more suitable for data extraction from larger population groups, and allowed for the measurement and testing of variables using statistical methods and procedures (McCusker and Gunaydin, 2015). Data were collected from a two-day 2017 Norwegian full-scale maritime chemical oil-spill pollution exercise with partners from Norway, Germany, Iceland, Denmark and Sweden. The exercise included international public emergency response organizations and Norwegian non-governmental organizations. The study was approved by the Norwegian Centre for Research Data (ref. 44815) and the exercise planning organization. Data were collected using the collaboration, learning and utility (CLU) scale, which is a validated instrument designed to measure exercise participant's perceived levels of collaboration, learning and usefulness (Berlin and Carlström, 2015). Findings: The perceived focus on collaboration, learning and usefulness changed with the number of previous exercises attended. All CLU dimensions experienced decreases and increases, but while perceived levels of collaboration and utility reached their somewhat modest peaks among those with the most exercise experience, perceived learning was at its highest among those with none or little exercise experience, and at its lowest among those with most. These findings indicated that collaboration exercises in their current form have too little focus on collaborative learning. Research limitations/implications: Several limitations of the current study deserve to be mentioned. First, this study was limited in scope as data were collected from a limited number of participants belonging to only one organization and during one exercise. Second, demographical variables such as age and gender were not taken into consideration. Third, limitation in performing a face-to-face data collection may have resulted in missing capturing of cues, verbal and non-verbal signs, which could have resulted in a more accurate screening. Moreover, the measurements were based on the predefined CLU-items, which left room for individual interpretation and, in turn, may cause somewhat lower term validity. As the number of international and national studies on exercise effects is scarce, it is important to increase further knowledge and to learn more about the causes as to why the perceived effects of collaboration exercises are considered somewhat limited. Practical implications: Exercise designers may be stimulated to have a stronger emphasis on collaborative learning during exercise planning, hence continuously work to develop scripts and scenarios in a way that leads to continuous participant perceived learning and utility. Social implications: Collaboration is established as a Norwegian national emergency preparedness principle. These findings may stimulate politicians and top crisis managers to develop national collaboration exercise script guidelines that emphasize collaborative learning and development. Originality/value: This study shows how exercise experience impacted participant's perceived levels of collaboration, learning and usefulness. Findings indicated that collaboration exercises in their current form have too little focus on collaborative learning.